Phloem long‐distance delivery of FLOWERING LOCUS T (FT) to the apex. (14th May 2013) - Yoo, Soo‐Cheul; Chen, Cheng; Rojas, Maria; Daimon, Yasufumi; Ham, Byung‐Kook; Araki, Takashi; Lucas, William J.
Summary: Cucurbita moschata FLOWERING LOCUS T‐LIKE 2 (hereafter FTL2) and Arabidopsis thaliana (Arabidopsis) FLOWERING LOCUS T (FT), components of the plant florigenic signaling system, move long‐distance through the phloem from source leaves to the vegetative apex where they mediate floral induction. The mechanisms involved in long‐distance trafficking of FT/FTL2 remain to be elucidated. In this study, we identified the critical motifs on both FT and FTL2 required for cell‐to‐cell trafficking through mutant analyses using a zucchini yellow mosaic virus expression vector. Western blot analysis, performed on phloem sap collected from just beneath the vegetative apex of C. moschata plants, established that all mutant proteins tested retained the ability to enter the phloem translocation stream. However, immunolocalization studies revealed that a number of these FTL2/FT mutants were defective in the post‐phloem zone, suggesting that a regulation mechanism for FT trafficking exists in the post‐phloem unloading step. The selective movements of FT/FTL2 were further observed by microinjection and trichome rescue studies, which revealed that FT/FTL2 has the ability to dilate plasmodesmata microchannels during the process of cell‐to‐cell trafficking, and various mutants were compromised in their capacity to traffic through plasmodesmata. Based on these findings, a model is presented to account for the mechanism by which FT/FTL2 enters the phloem translocation stream and subsequently exits the phloem and enters the apical tissue, where it initiates the vegetative to floral transition.